Recursos didácticos en la enseñanza - aprendizaje de los Estudios Sociales, en los niños de quinto grado A, de la Unidad Educativa Padre Julián Lorente, de la ciudad de Loja, periodo 2018 – 2019. Lineamientos alternativos - Patiño Abad, Andrea Maribel (2019)
The present research work Teaching resources in the teaching - learning of Social Studies, in children in fifth grade A, of the Father Julián Lorente Educational Unit, in the city of Loja, period 2018 - 2019. Alternative guidelines; it arises because the learning of Social Studies has long been considered a theoretical process, due to the bad pedagogical practice that teachers have used in forging a traditional education; resulting in uncreative students because of factors such as the scarpce application of teaching resources, content not in accordance with the needs and interests of infants and lack of interest in training in new forms of teaching, does this lead to asking the following questions? How does the absence of teaching resources affect the teaching-learning process in children? and How to help the didactic resources to the students in their learning? Posing as an objective: to identify the effect of teaching resources on the teaching - learning of Social Studies, in children in fifth grade A, of the Father Julián Lorente Educational Unit, in the city of Loja, period 2018 - 2019. The same that was supported through the descriptive study and the methods applied: descriptive, observational, analytical, synthetic, inductive, deductive, hermeneutical; The survey technique was used as an instrument, the questionnaire and the procedures used were: theoretical basis, to establish the relationship teaching resources and teaching - learning and the design of the alternative guidelines. The population is made up of a teacher and sixteen students.